Embolic strokes of undetermined source in young adults: baseline characteristics and long‐term outcome. (19th January 2018) - Martinez‐Majander, N.; Aarnio, K.; Pirinen, J.; Lumikari, T.; Nieminen, T.; Lehto, M.; Sinisalo, J.; Kaste, M.; Tatlisumak, T.; Putaala, J.
Abstract : Background and purpose: Embolic strokes of undetermined source (ESUS) are a recent entity, not yet thoroughly investigated in young stroke patients. The clinical characteristics and long‐term risks of vascular events and all‐cause mortality between young‐onset ESUS and other aetiological subgroups were compared. Methods: Patients with ESUS were identified amongst the 1008 patients aged 15−49 years with first‐ever ischaemic stroke in Helsinki Young Stroke Registry, and primary end‐points were defined as recurrent stroke, composite vascular events and all‐cause mortality. Cumulative 15‐year risks for each end‐point were analysed with life tables and adjusted risks were based on Cox proportional hazard analyses. Results: Of the 971 eligible patients, 203 (20.9%) were classified as ESUS. They were younger (median age 40 years, interquartile range 32–46 vs. 45 years, 39–47), more often female (43.3% vs. 35.7%) and had fewer cardiovascular risk factors than other modified TOAST groups. With a median follow‐up time of 10.1 years, ESUS patients had the second lowest cumulative risk of recurrent stroke and composite vascular events and lowest mortality compared to other TOAST groups. Large‐artery atherosclerosis and small vessel disease carried significantly higher risk for recurrent stroke than did ESUS, whilst no difference appeared between cardioembolism from high‐risk sources and ESUS. Conclusions: In our cohort, ESUS patients were younger and had milder cardiovascular risk factor burden and generally better long‐term outcome compared to other causes of young‐onset stroke. The comparable risk of recurrent stroke between ESUS and high‐risk sources of cardioembolism might suggest similarities in their pathophysiology.